Optimization of a Treatment Protocol for Acute Stenosing Laryngitis in Children - L. V. Kramar; T. Y. Larina (LLC "Diagnostics and Vaccines", 2016)
Submitted by optimizing the treatment of acute stenosing laryngitis (croup) in children. The use of short courses of topical and systemic corticosteroids showed high clinical efficiency, shortening hospital stay, good tolerability and absence of side effects.